Filósofos en 90 minutos. (Pack 3), (Maquiavelo, Berkeley, Leibniz, Spinoza, Hume y Descartes) - Strathern, Paul, 1940-; Strathern, Paul, 1940-; Strathern, Paul, 1940-; Strathern, Paul, 1940-; Strathern, Paul, 1940-; Strathern, Paul, 1940-; Strathern, Paul, 1940- (Tres Cantos, Madrid, España : Siglo XXI de España Editores, S.A., 2017)
The Pack Filósofos 3 collection brings together 6 of the most outstanding philosophers of the Modern Age.
Maquiavelo en 90 minutos -- Berkeley en 90 minutos -- Leibniz en 90 minutos -- Spinoza en 90 minutos -- Hume en 90 minutos -- Descartes en 90 minutos.
This collection of books by Strathern were published separately in print. The publisher now combined them by subject and published them together in digital format.
Includes bibliographical references.
Online resource; title from ePub title page (Digitalia, viewed February 7, 2019)
Keywords: Machiavelli, Niccolò, -- 1469-1527.; Berkeley, George, -- 1685-1753.; Leibniz, Gottfried Wilhelm, -- Freiherr von, -- 1646-1716.; Spinoza, Benedictus de, -- 1632-1677.; Hume, David, -- 1711-1776.; Descartes, René, -- 1596-1650.; Philosophers -- Biography; Biographies; Electronic books